Potential utility of miRNAs for liquid biopsy in breast cancer - Liu, Xiangrong; Papukashvili, Dimitri; Wang, Zhixiang; Liu, Yan; Chen, Xiaoxia; Li, Jianrong; Li, Zhiyuan; Hu, Linjie; Li, Zheng; Rcheulishvili, Nino; Lu, Xiaoqing; Ma, Jinfeng (Frontiers in Oncology, 2022)
Breast cancer (BC) remains the most prevalent malignancy due to its incidence rate, recurrence, and metastasis in women. Conventional strategies of cancer detection– mammography and tissue biopsy lack the capacity to detect the complete cancer genomic landscape. Besides, they often give false- positive or negative results. The presence of this and other disadvantages such as invasiveness, high cost, and side effects necessitates developing new strategies to overcome the BC burden. Liquid biopsy (LB) has been brought to the fore owing to its early detection, screening, prognosis, simplicity of the technique, and efficient monitoring. Remarkably, microRNAs (miRNAs)– gene expression regulators seem to play a major role as biomarkers detected in the samples of LB. Particularly, miR-21 and miR-155 among other possible candidates seem to serve as favorable biomarkers in the diagnosis and prognosis of BC. Hence, this review will assess the potential utility of miRNAs as biomarkers and will highlight certain promising candidates for the LB approach in the diagnosis and management of BC that may optimize the patient outcome.